Functional Consequences of Reduction in NMDA Receptor Glycine Affinity in Mice Carrying Targeted Point Mutations in the Glycine Binding Site - Kew, James N. C. (J Neurosci, 2000)
We have used site-directed mutagenesis in conjunction with homologous recombination to generate two mouse lines carrying point mutations in the glycine binding site of the NMDAR1 subunit (Grin1). Glycine concentration–response curves from acutely dissociated hippocampal neurons revealed a 5- and 86-fold reduction in receptor glycine affinity in mice carryingGrin1(D481N) andGrin1(K483Q)mutations, respectively, whereas receptor glutamate affinity remained unaffected. Homozygous mutant Grin1(D481N)animals are viable and fertile and appear to develop normally. However, homozygous mutant Grin1(K483Q)animals are significantly lighter at birth, do not feed, and die within a few days. No gross abnormalities in CNS anatomy were detected in either Grin1(D481N)orGrin1(K483Q)mice. Interestingly,in situ hybridization and Western blot analysis revealed changes in the expression levels of NMDA receptor subunits inGrin1(D481N)mice relative to wild type that may represent a compensatory response to the reduction in receptor glycine affinity. Grin1(D481N)mice exhibited deficits in hippocampal theta burst-induced long-term potentiation (LTP) and spatial learning and also a reduction in sensitivity to NMDA-induced seizures relative to wild-type controls, consistent with a reduced activation of NMDA receptors. Mutant mice exhibited normal prepulse inhibition but showed increased startle reactivity. Preliminary analysis indicated that the mice exhibit a decreased natural aversion to an exposed environment. The lethal phenotype of Grin1(K483Q)animals confirms the critical role of NMDA receptor activation in neonatal survival. A milder reduction in receptor glycine affinity results in an impairment of LTP and spatial learning and alterations in anxiety-related behavior, providing further evidence for the role of NMDA receptor activation in these processes.